FORECASTING THE FOOD GAP AND PRODUCTION OF WHEAT CROP IN IRAQ FOR THE PERIOD (2016-2025) - & Jbara, Mustafa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Wheat is an important economic crop, various development projects adopted by the government to improve the level of production of all crops Despite the efforts to increase the production of grain crops, especially the wheat, the total production is still insufficient to meet the growing consumption needs, which led to widening of the food gap in addition to the increase in population and the increasing demand for food.The aim of this research is to Forecasting food gap and production of wheat in Iraq, Box-Jenkins one of forecasting method used to forecast production and food gap of wheat. Statistical programs Minitab and SPSS used to analyses data. The best method for Forecasting wheat production for the period 2025-2016 is ARIMA (4,1,3) based on significance of its parameters, as well as for having the lowest value of MSE which reached and owning the lowest value for(AIC). About food gap, the ARIMA model (1.0.1) was the best model for the same period in terms of having the lowest value (MSE) and the lowest value of AIC. The research reached a set of conclusions, There is an increase in the production of wheat in Iraq during the coming years (2025-2016) while offset by a semi-constant in the food gap for the same period and this indicates that the self-sufficiency of wheat in the short run can’t occur. Food gap for wheat is continuous and semi-fixed, indicating the expectation that self-sufficiency can’t be achieved in the short term, and the difficulty of covering consumption through the local production of wheat and having to fill the deficit by importing semi-fixed quantities during the subsequent period.